Study of Biological Activity and Chemical Constituent of Annona Reticulata - Subba, Bimala; Aryal, Pramod (Journal of Institute of Science and Technology, 2016)
The methanol and hexane extract of leaf of Annona reticulata, vernacularly known as ‘Sareefa’ were subjected to biological assay and column chromatography respectively. Column chromatography of the hexane extract of the leaf of A. reticulata resulted in the isolation of one pure compound PF1. The compound PF1 was suggested as β-sitosterol by comparing TLC, IR and melting point with authentic sample. The antibacterial activity against two bacteria, Staphylococcus aureus (gram positive) and Escherichia coli (gram negative) was done by agar well diffusion method and Zone of Inhibition (ZOI) was observed. The ZOI obtained ranged from 8 to 12 mm. The methanol extract of leaf showed moderate antibacterial activity on comparison with standard antibiotic streptomycin. The Antioxidant activity of the extract was tested using scavenging activity of DPPH (1, 1-Diphenyl-2- Picrylhydrazyl) radical method. The IC50 value of A. reticulata was found (41 µg/ml). The standard compound has shown IC50 value as 120 µg/ml. The antimicrobial and antioxidant activity of the extract was positively associated with the total phenolic and flavonoid contents of the extract. This study revealed that methanolic leaf extract of A. reticulata comprise effective potential source of natural antioxidant, which might be helpful in preventing the progress of various oxidative stresses. Journal of Institute of Science and Technology Volume 21, Issue 1, August 2016, page: 157-163